Analisis Potensi Sektor Ekonomi Pada Kabupaten Dan Kota Provinsi Daerah Istimewa Yogyakarta - Shinta Iffah Rosyidah (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2022)
Regional growth in the present era of regional autonomy will be fraught with challenges. This is a result of regional disparities, the advent of globalization, and the fierce rivalry across areas. The province of Daerah Istimewa Yogyakarta (DIY) possesses one city and four districts constitute. Each municipality/district has its own GRDP and economic potential. This helps an area raise its competitiveness so that it can improve the well-being of its citizens. This research employs a quantitative method to identify the top sectors in DIY municipalities/districts for 2018-2021. According to the findings of the LQ analysis, there are several basic sectors, including seven in Sleman Regency, six in Bantul Regency, eleven in Yogyakarta City, eight in Kulonprogo Regency, and seven in Gunungkidul Regency. Several sectors showed both positive and negative outcomes based on the Shift Share analysis. Meanwhile, According to the findings of Klassen's typology analysis, there are sectors in quadrant I, quadrant II, quadrant III, and quadrant IV.